Evaluation of near versus far target visual focus strategies with breaking putts - MacKenzie, S. J.; MacInnis, N. R. (International Journal of Golf Science, 2017)
The purpose of this study was to compare near-target (NT) and far-target (FT) visual focus strategies during the stroke on breaking putts. The ball was considered the NT and the FT was the point along the target line closest to the hole. Over three testing session, 28 golfers completed an equal number of putts for each combination of three independent variables: Method (NT, FT), Putt Length (6, 10, 14 ft), and Break (toe-to-heel, heel-to-toe) for a total of 144 putts. The FT method was associated with a significantly higher make percentage (40%) in comparison with the NT (37%), (p = .047). There was also a significant Method x Break interaction (p = .041); the FT method was relatively more effective for heel-to-toe breaking putts (41%) than the NT method (36%). These findings suggest that a FT visual strategy could be effective for golfers on breaking putts inside 14 ft. ABSTRACT FROM AUTHOR